The Impact of Higher Education Enrollment on Per Capita GDP in the Yangtze River Delta: An Analysis Based on BCC-DEA and Spatial Econometric Models - Sun, Haidong (Community and Social Development Journal, 2025)
The Yangtze River Delta (YRD) is a key driver of China's economic growth, with higher education playing a critical role in fostering regional economic development. This study uses the BCC-DEA model and spatial econometric methods with 2022 data to evaluate the efficiency of regular higher education enrollment in contributing to per capita GDP and explores its spatial distribution. The results reveal significant regional disparities in resource allocation, with some cities being DEA-efficient, such as Zhoushan, Wuxi, and Xuancheng (TE = 1), while others exhibit inefficiencies, including Shanghai (TE = 0.15; SE = 0.338) and Hefei (TE = 0.032; SE = 0.934). Spatial correlation between higher education resources and per capita GDP is weak, with Moran’s I = −0.073, and OLS regression shows a mismatch between educational resources and economic development, with the coefficient of enrollment (−0.017, p = 0.694) and low explanatory power (R² = 0.094; adjusted R² = −0.359). This study provides theoretical insights and policy recommendations for optimizing resource allocation and promoting coordinated development between higher education and the economy in the YRD region.